139 Can processed EEG improve our ability to monitor status epilepticus?. Issue 6 (27th May 2022) - Gimson, Amy; Smith, Matthew
Abstract : Processed electroencephalogram (EEG) is being increasingly used in operative anaesthetic practice for monitoring depth of anaesthesia. This potentially provides a frequently available, cost effective and simple to interpret method for monitoring status-epilepticus. This is important as continuous formal EEG monitoring (the NICE gold standard) is not available in most critical care environments. We undertook a systematic review of the evidence for using processed EEG for this indication. Literature was available for many of the processed EEG systems now available, with most concerning the Bispectral Index (BIS) device. This equipment provides a numerical value indicative of extent of burst suppression, which correlates to burst suppression observed on standard EEG recordings. Multiple case reports and eight prospective studies report the use of BIS for optimisation of burst suppression in patients with status-epilepticus at the bedside. Further reports suggest the ability of processed EEG to detect the presence of non-convulsive status-epilepticus. Evidence also exists from prospective studies performed during electro-convulsive therapy, providing a predictable model for examining the utility of processed EEG interpretation. We conclude that processed EEG may be helpful in monitoring clinical response in the treatment of status epilepticus, however additional prospective studies are required to provide a robust evidence base. a.gimson@nhs.net